Lot’s Wife is Still Standing: In Search of the Pillar of Salt - Low, Katherine (Journal of the bible and its reception, 2021)
This article explores how readers search for Lot’s wife at the shore of the Dead Sea and how they use the pillar of salt as a destination, as a symbol, and as a lasting memorial. Whether Lot’s wife turned into a pillar of salt that travelers to the Dead Sea can visit today is not relevant for this analysis. Spanning many centuries, this reception history of Lot’s wife argues that readers use her for their own interests to address their own cultural concerns. Three chronological areas are addressed for a broad-sweeping coverage of some trends and traditions about Lot’s wife. While the Hebrew text remains ambivalent about memorializing Lot’s wife, Hellenistic Jewish and early Christian sources reveal a concern to remember Lot’s wife in terms of God’s final judgments. The article then turns to medieval Christian travel narratives and maps that use Lot’s wife to mark the borders of Christendom, with pilgrims seeking her amid Crusades-era concerns. Finally, modern sources are discussed that deal with Lot’s wife in terms of symbolizing sexual trauma, deviance, and danger. Gender theory and queer theory are utilized in the article as secondary ideological lenses through which to engage reception history. What results is a complex picture regarding how people use Lot’s wife to negotiate boundaries, engage biblical myth, and further their own agendas.